Amelioration of elastase‐induced lung emphysema and reversal of pulmonary hypertension by pharmacological iNOS inhibition in mice. (28th April 2020) - Fysikopoulos, Athanasios; Seimetz, Michael; Hadzic, Stefan; Knoepp, Fenja; Wu, Cheng‐Yu; Malkmus, Kathrin; Wilhelm, Jochen; Pichl, Alexandra; Bednorz, Mariola; Tadele Roxlau, Elsa; Ghofrani, Hossein A.; Sommer, Natascha; et al.
Abstract : Background and Purpose: Chronic obstructive pulmonary disease, encompassing chronic airway obstruction and lung emphysema, is a major worldwide health problem and a severe socio‐economic burden. Evidence previously provided by our group has shown that inhibition of inducible NOS (iNOS) prevents development of mild emphysema in a mouse model of chronic tobacco smoke exposure and can even trigger lung regeneration. Moreover, we could demonstrate that pulmonary hypertension is not only abolished in cigarette smoke‐exposed iNOS −/− mice but also precedes emphysema development. Possible regenerative effects of pharmacological iNOS inhibition in more severe models of emphysema not dependent on tobacco smoke, however, are hitherto unknown. Experimental Approach: We have established a mouse model using a single dose of porcine pancreatic elastase or saline, intratracheally instilled in C57BL/6J mice. Emphysema, as well as pulmonary hypertension development was determined by both structural and functional measurements. Key Results: Our data revealed that (i) emphysema is fully established after 21 days, with the same degree of emphysema after 21 and 28 days post instillation, (ii) emphysema is stable for at least 12 weeks and (iii) pulmonary hypertension is evident, in contrast to smoke models, only after emphysema development. Oral treatment with the iNOS inhibitor N(6)‐(1‐iminoethyl)‐l ‐lysine (L‐NIL) was started after emphysema establishment and continued for 12 weeks. This resulted in significant lung regeneration, evident in the improvement of emphysema and reversal of pulmonary hypertension. Conclusion and Implications: Our data indicate that iNOS is a potential new therapeutic target to treat severe emphysema and associated pulmonary hypertension. LINKED ARTICLES: This article is part of a themed issue on Risk factors, comorbidities, and comedications in cardioprotection. To view the other articles in this section visit http://onlinelibrary.wiley.com/doi/10.1111/bph.v178.1/issuetoc